Eight New Late Pleistocene/Early Holocene AMS Dates from the Southeastern Baltic. Issue 2 (29th January 2019) - Philippsen, Bente; Ivanovaitė, Livija; Makhotka, Kirill; Sauer, Florian; Riede, Felix; Olsen, Jesper
ABSTRACT: Only a limited number of radiometric dates for the Final Palaeolithic and the first half of the Mesolithic are available from the southeastern Baltic. This paper presents eight new Late Pleistocene/Early Holocene radiocarbon accelerator mass spectrometry ( 14 C AMS) ages of osseous artifacts housed at the Kaliningrad Regional Museum of History and Art. These artifacts include one piece of worked reindeer ( Rangifer tarandus ) antler, three axes of the so-called Lyngby type, one bone point, one uniserial harpoon, one so-called bâton percé antler shaft, and one slotted bone. All the samples were successfully dated and yielded five Late Pleistocene and three Early Holocene ages, including the hitherto earliest age for human occupation in the Eastern Baltic. The dates include not only a surprisingly early date for a bone point (for this region), but also some dates that contradict expected ages based on traditional typological assessment. Our study significantly adds to the still small number of existing absolutely dated artifacts from the region and proposes new ways of viewing the Final Palaeolithic and Early Mesolithic chronology in the southeastern Baltic.